Strengthening lupus education and coordinated care in developing countries - Navarra, Sandra V. (Frontiers in Lupus, 2024)
SLE is a chronic autoimmune disease with a wide range of manifestations and potential to affect several organ systems. Complications arise from both disease and medications especially glucocorticoids, significantly contributing to overall morbidity and mortality. SLE predominantly affects patients during their prime productive years resulting in substantial economic burden on the patient, caregivers and society due to direct, indirect and intangible costs. In developing countries with limited resources, efficient healthcare delivery for most lupus patients remains elusive. This is magnified by the increasing shortage of rheumatologists and lupus specialists. Physician education starting in medical school as well as practical referral pathways and physician networking in clinical practice ensure continuity of and coordinated care for every lupus patient. Likewise, education of allied health professionals, patient empowerment and self-help programs help improve overall outcomes in SLE.